Linfoma multicêntrico em búfalos no Brasil: etiologia, patologia e clínica - Cairo Henrique Sousa de Oliveira (2015)
In this study we described for the first time the occurrence of lymphoma in buffaloes from Brazil and conducted a clinical, etiological and pathological research. Although some authors described this disease as enzootic bovine leucosis in buffalo, the etiologic agent Bovine leukemia virus (BLV) was not detected in 314 buffalos serum and whole blood samples from herds with and without lymphoma history. Serum samples were evaluated by AGID and ELISA, and whole blood by two PCRs. Bovine herpesvirus 6 (BoHV-6) was detected in 2.23% of these samples by seminested PCR. Despite the oncogenic potential of gammaherpesvirus, as Epstein Barr virus (EBV) associated with lymphoma occurrence in humans, BoHV-6 has no defined role as illness agent in cattle and was detected for the first time in buffaloes. By immunohistochemistry was found that the neoplastic disease in buffaloes was characterized by B cell multicentric lymphoma. The mainly clinical signs were lymphadenopathy and progressive weight loss, in the pathology can be observed miliary nodules on organs serous and large tumor masses with different body locations. We detected Bovine immunodeficiency virus (BIV) in tumor samples, kidney and lymph nodes from a sick buffalo, what indicates it is important to consider the indirect role of lentivirus as cancer-inducing agent.